Investigating the Nexus between Crude Oil Price and Stock Prices of Oil Exploration Companies - Kumar, K. Abhaya; Pinto, Prakash; Hawaldar, Iqbal Thonse; Shaikh, Saheem; Bhagav, Shravan; Padmanabha, B. (International Journal of Energy Economics and Policy, 2022)
In emerging economies, examining the linkage between different markets has become crucial. We have examined the linkage between crude oil and Indian oil exploration companies' equity prices. The augmented Dickey-Fuller method is used to test the stationarity of the series. The Granger causality test, Vector autoregression (VAR), and correlation methodologies are used to examine the causality between the markets. The p-values of Granger causality tests are less than 0.05, which confirms that the crude oil price causes the price movements of Indian oil exploration equities. The VAR (2) model confirmed that the prices of HOCE, OIL, and ONGC follow the first and second lag, Reliance and PETRONET equities follow the first lag of International crude price. The impulse response function shows a positive response of Indian oil exploration equity returns for the positive shocks of crude oil return. The findings of this study may help the traders and investors in the equity market, energy equity investors.